2020
DOI: 10.2298/hemind20060523s
|View full text |Cite
|
Sign up to set email alerts
|

Global sensitivity analyses of a neural networks model for a flotation circuit

Abstract: Modeling of flotation processes is complex due to the large number of variables involved and the lack of knowledge on the impact of operational parameters on the response(s), and given this problem, machine learning algorithms emerge as an alternative interesting when modeling dynamic processes. In this work, different artificial neural network (ANN) architectures for modeling the mineral concentrate in a rougher-cleaner-scavenger (RCS) circuit based on the main process variables are gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The general ANN model, used in this study, consisted of input, hidden and output layers, as it is shown in Figure 2. [17,18]. The ANN has two neurons in the input layer (time and temperature), selected to predict the torque as a single neuron in the output layer.…”
Section: Artificial Neural Network Developmentmentioning
confidence: 99%
“…The general ANN model, used in this study, consisted of input, hidden and output layers, as it is shown in Figure 2. [17,18]. The ANN has two neurons in the input layer (time and temperature), selected to predict the torque as a single neuron in the output layer.…”
Section: Artificial Neural Network Developmentmentioning
confidence: 99%
“…The mining industry in Chile is constantly growing [1][2][3][4] . Historically, Chile has traded copper, this commodity being the main economic income contributing approximately 10 % of the gross domestic product (GDP) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of copper minerals in the world correspond to sulfide minerals and a smaller quantity to oxidized minerals [5][6][7][8]. Among the sulfurous minerals, the most abundant copper mineral is chalcopyrite [9][10][11], followed by chalcocite [12].…”
Section: Introductionmentioning
confidence: 99%